Taxa de monócitos e de linfócitos e reação de Mitsuda em indivíduos sadios não comunicantes de hansenianos - VOZZA, J. A. (1977)
The frequency of monocytes, lymphocytes and monocytes plus lymphocytes was investigated in two samples of healthy Brazilian soldiers who were inoculated intradermally with 0.1 ml of standard lepromin. Their ages varied from 18 to 20 years and none of them were contacts of leprosy patients. One sample was composed of 87 individuals (40 negative, 33 moderately positive and 14 strongly positive Mitsuda reactors) and the other included 96 persons (57 negative, 28 moderately positive and 11 strongly positive Mitsuda reactors). In both samples the mean frequency of monocytes presented by the strongly positive Mitsuda reactors was face value, though not significantly, higher than those presented by the moderately positive and negative Mitsuda reactors. This tendency was not observed in the mean frequencies of lymphocytes and monocytes plus lymphocytes, which did not differ significantly among the groups of individuals belonging to the three classes of Misuda's reactions.